A Balanced Act: The Effects of GH–GHR–IGF1 Axis on Mitochondrial Function - Hu, Bowen; Li, Hongmei; Zhang, Xiquan (Frontiers in Cell and Developmental Biology, 2021)
Mitochondrial function is multifaceted in response to cellular energy homeostasis and metabolism, with the generation of adenosine triphosphate (ATP) through the oxidative phosphorylation (OXPHOS) being one of their main functions. Selective elimination of mitochondria by mitophagy, in conjunction with mitochondrial biogenesis, regulates mitochondrial function that is required to meet metabolic demand or stress response. Growth hormone (GH) binds to the GH receptor (GHR), and induces the JAK2/STAT5 pathway to activate the synthesis of insulin-like growth factor 1 (IGF1). GH-GHR-IGF1 axis has been recognized to play significant roles in somatic growth, including cell proliferation, differentiation, division and survival. In this review, we describe recent discoveries providing evidence for the contribution of GH-GHR-IGF1 axis on mitochondrial biogenesis, mitophagy (or autophagy), and mitochondrial function under multiple physiological conditions. This may further improve our understanding of the effects of GH-GHR-IGF1 axis on mitochondrial function, which may be controlled by the delicate balance between mitochondrial biogenesis and mitophagy. Specifically, we also highlight the challenges that remain in this field.